(Re)produção de sentidos em partidos políticos brasileiros: uma análise do núcleo manifesto das marcas Podemos, Avante e Patriota - Petitinga Júnior, Paulo Roberto Lima (2019)
Brazilian voters have been surprised by lots of rebranding decisions by political parties, mainly in the last decade. Nevertheless, this movement isn’t recent: It’s started in the 1990’s and intensify twenty years late as a response to the risks generated by the approval of a kind of performance prerequisite which have will interfere in some benefits of political parties that no would reach determinate electoral goals. Besides that, the Brazilian political system has been affected by a deep representation’s crisis among the voters, fostered by the continuing corruption’s scandals involving political agents. Nevertheless, for some Brazilian political parties the brand’s change isn’t only a choice but one last attempt to rebuild its organizational image among its voters. This study sought to investigate the construction of meanings associated with the Brazilian political parties’ brand changes. For this, we analyzed the political parties as social systems crated though communication efforts. So, we began our analysis with the premise that brands are a relevant phenomenon for the postmodern society, because of its symbolism and ability to show which is (or even isn't) the organization it's embodying. As result of our empiricus effort, it’s possible to understand that the Brazilian political parties operate a kind of autopoiesis to avoid a possible structural decoupling from its environment, handling Brazilian's recognized narratives to produce new discourses, then it was been possible to reduce the risks inherent in this organizational renew.